VALORIZATION OF SIDA CORDIFOLIA L. BIOMASS IN COMPOST FOR PEARL MILLET (PENNISETUM GLAUCUM) PRODUCTION IN NIGER - Sadi Souley, Maman; SAIDOU, ADDAM KIARI; Morou, Boubé; B. Aune, Jens (International Journal of Research -GRANTHAALAYAH, 2020)
Sida cordifolia L. (SC) is an invading species that represents a threat to grazing lands in Niger. In order to enhance this invasive species, we studied the use of this plant for compost-making. First, the study evaluated the development of chemical properties under aerobic composting of SC in pit (P) and in heap (H) composting with two different mixtures. Mixture 1 (M1) contained 75% SC, 20% manure and 5% ash, while mixture 2 (M2) contained 95% SC and 5% manure. Then, the phytotoxicity test of the composts obtained was carried out by evaluating the effects of four different concentrations of compost on germination of pearl millet. The study of the effect of the rates 1000 kg ha-1 and 1500 kg ha-1 (100g and 150 g hill-1) of the different composts on pearl millet yield under field conditions. The composting was undertaken at Molli fishery station and the agronomic tests at the N’Dounga experimental site during two seasons (2018 and 2019). The chemical analysis showed that the composts from M1 were richer in plant nutrients than the M2 composts. All four rates of composts gave germination rates beyond 50% independent of composting method or compost mixture. On both seasons, the 1000 kg ha-1 M1P gave the best result in terms of grain yield. In 2018, M1P treatment increased grain yield compared to the control by 652 kg ha-1 (105.2%), while in 2019, the corresponding yield increase was 812 kg ha-1 (118.02%). Application of 1000 kg M1 compost ha-1 corresponded to about 11.1 kg N ha-1, which is more than three times the amount of N applied when using the recommended rate of 20 kg NPK ha-1 as micro dosing. This result showed that compost of SC can be used as a supplement to mineral fertilizer for increasing pearl millet yield.